Provisional measures’ application in custody hearings: a study based on homeless people’ arrests. - Vinícius de Assis Romão (Revista Brasileira de Direito Processual Penal, 2021)
The article’s question is about how provisional measures are applied in encounters between legal actors and homeless people in custody hearings, based on the procedural of debating and deciding. Data collection took place at the Núcleo de Prisão em Flagrante e Audiências de Custódia in Salvador, in two periods of the year 2018, to understand the meanings conferred by judges, prosecutors and defenders regarding provisional measures in kind. Among the observation of hearings with 69 in custody, the research had as an operational sample cases of 19 people living on the streets. In relation to these, a documentary analysis was also carried out of the 19 flagrant arrest records and 52 past cases, including criminal actions and flagrant arrest records, which were recorded as criminal records. Expanding the analysis beyond the mere absence or insufficiency of reasoning in the decisions and analyzing the “paredão” technique as an informal hearing procedure, the hidden features that have been attributed to the provisional measures were analyzed, in each context of punitive demand, along the logic of “perspective prison”. The work concludes that the measures considered as alternatives, in addition to not being discussed under the legal criteria, exercise a punitive anticipation function and are inserted in the urban socio-racial management, presenting deeper connections with the pre-trial prison, which is maintained in its horizon.